Nickel recovery from nickel-containing spent catalyst using atmospheric leaching and oxalate precipitation - Widi Astuti; Yuniati, Mutia Dewi; Yuda, Aulia Pertiwi Tri; Sumardi, Slamet; Dewi, Jilda Sofiana; Wanta, Kevin Cleary; Petrus, Himawan Tri Bayu Murti (Jurnal Rekayasa Proses, 2025)
A study has been done to investigate and optimize the recovery of nickel from nickel-containing spent catalyst through sulfuric acid (1 - 2 mol/L) atmospheric leaching in different operation conditions. From the leaching experiments, it was possible to extract 77.95% nickel under the conditions of 2 mol/L H2SO4, reaction time of 5 h, 5% pulp density, and temperature of 80°C. In the next step Ni was selectively precipitated from a sulfuric acid-leached solution using 1 mol/L oxalic acid. The nickel content in the product was 97.29% Ni. Based on the study, sulfuric acid was found to be a suitable leaching agent to extract Ni from the nickel-containing spent catalyst. The study also indicated the effective extraction and recovery of nickel which was well supported by characterization studies using XRD technique.